The association between emotions and eating behaviour in an obese population with binge eating disorder. (8th December 2015) - Nicholls, W.; Devonport, T. J.; Blake, M.
Summary: There is utility in understanding the antecedents of binge eating (BE), with a view to explaining poorer weight loss treatment responses in this subgroup. A systematic review was completed according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines with the aim of exploring associations between emotions and eating behaviour in a population affected by obesity and binge eating disorder (BED). A comprehensive literature search of four electronic databases (2004–2014) yielded 15 studies for inclusion. Included studies performed poorly on data quality analysis with respect to controlling for confounding variables, and sample size. Included papers largely focused on negative emotions as antecedents of BE; depression was consistently associated with a BED‐obese classification and BE. Negative mood, sadness, tension and instability of emotions were found to be antecedents of BE in an adult BED‐obese sample. However, findings were mixed regarding the role of stress, anger and positive emotions within the BED‐obese population. Recommendations are presented for the identification of BED, and ecologically valid experimental designs that further understanding of the complex and varied emotions that associate with BE. The implications of these and other limitations for both researchers and practitioners are discussed. The paper concludes with recommendations for future research alongside suggestions for practitioners. © 2015 World Obesity